Halal tourism based on local wisdom in Madura: Opportunities and challenges - Saifulloh Saifulloh; Betania Kartika; Mohamad Afiq bin Razali; Muhammad Aizat Jamaludin (Yayasan Azhar Amanaa Yogyakarta, 2024)
Religious and spiritual tourism have been increasingly common and well-liked in recent decades, representing a large portion of global travel and expanding rapidly in recent years. The phrase